Ocenka urovnja fiziceskoj podgotovlennosti detej 6-10 let s raznymi vidami sportivnoj specializaci - Polfuntikova, A.V.; Abramova, T. F.; Nikitina, T. M.; Akopyan, A. O.; Kulagina, L. A.; Mikhalev, S. V.; Stashkevich, S. S.; Oblog, K. A.; Shuvalova, L. S.; Iordanskaya, F. A.; Buchina, E. V.; Yashina, E. R. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The specificity of the influence of various types of physical activity on the physical fitness of children 6-10 years old was studied. Pedagogical testing of children involved in various types of sports activities was carried out: playing (football), cyclic (cycling-BMX), single combats (judo, freestyle wrestling), as a control - a group of children not involved in sports (NZS). The testing program included: hand dynamometry; jump from a place with two legs; shuttle run (10m×3); lean forward from a standing position. To assess the physical qualities, the standards of educational institutions and the TRP standards were used. Individual assessment of physical fitness indicators included categories: low, medium or high. 462 boys aged 6-10 years were examined: 103 football players, 100 cyclists (BMX discipline), 109 boys involved in martial arts and 150 children not involved in sports.